The Uncanny Child in Transnational Cinema Ghosts of Futurity at the Turn of the Twenty-first Century - Balanzategui, Jessica (Film Culture in Transition, 2017)
The uncanny child in transnational cinema illustrates how global horror film images of children reconceptualised childhood at the beginning of the twenty-first century, unravelling the child's long entrenched binding to ideologies of growth, futurity, and progress. The book analyses an influential body of horror films featuring subversive depictions of children and proposes that complex cultural and industrial shifts at the turn of the millennium resulted in potent cinematic renegotiations of the concept of childhood. In these transnational films - largely stemming from Spain, Japan, and America - the child resists embodying growth and futurity: by demonstrating both the culturally specific and globally resonant properties of these frightening visions of children who refuse to grow up, the book outlines the conceptual and aesthetic mechanisms by which long entrenched ideologies of futurity, national progress, and teleological history started to waver at the turn of the 21st century.